Shallow water tomography in a highly variable scenario - Soares, C. (2014)
In October 2000, SiPLAB and the Instituto Hidrográfico (IH - PN) conducted the IN-TIFANTE’00 sea trial in a shallow area off the Peninsula of Tróia, approximately 50 km south from Lisbon, in Portugal. The experiment itself and results obtained in most of the data set have been reported at various occasions in the last two years. This paper focuses on the data acquired during Event 2, where the acoustic propagation path was approximately range independent and the source ship was held on station at a constant range of 5.8 km from the vertical line array. Although these conditions were, in general, relatively benign for matched-field tomography, retrieval of water column and bottom parameters over a 14-hour-long recording revealed to be extremely difficult. This paper analysis in detail the characteristics of this data set and determines the causes for the observed inversion difficulties. Is is shown that the causes for the poor performance of the conventional methods are mainly the tide induced spatially correlated noise and the relative source-receiver motion during time averaging. An eigenvalue-based criterion is proposed for detecting optimal averaging time. It is shown that this data selection procedure together with hydrophone normalization and an appropriate objective function provide a better model fit and consistent inversion results and thus a better understanding of the environmental variability.